Non-contrast preoperative MRI for determining renal perfusion and visualizing renal arteries in potential living kidney donors at 1.5 Tesla - Andersson, Julian; Meik, Rosalie; Pravdivtseva, Mariya S.; Langguth, Patrick; Gottschalk, Hannes; Sedaghat, Sam; Jüptner, Michael; Koktzoglou, Ioannis; Edelman, Robert R.; Kühn, Bernd; Feldkamp, Thorsten; Jansen, Olav; et al. (Clinical kidney journal, 2024)
BACKGROUND: The aim of this work was to create and evaluate a preoperative non-contrast-enhanced (CE) magnetic resonance imaging (MRI)/angiography (MRA) protocol to assess renal function and visualize renal arteries and any abnormalities in potential living kidney donors. - METHODS: In total, 28 subjects were examined using scintigraphy to determine renal function. In addition, 3D-pseudocontinuous arterial spin labeling (pCASL), a 2D-non-CE electrocardiogram-triggered radial quiescent interval slice-selective (QISS-MRA), and 4D-CE time-resolved angiography with interleaved stochastic trajectories (CE-MRA) were performed to assess renal perfusion, visualize renal arteries and detect any abnormalities. Two glomerular filtration rates [described by Gates (GFRG) and according to the Chronic Kidney Disease Epidemiology Collaboration formula (GFRCKD-EPI)]. The renal volumes were determined using both MRA techniques. - RESULTS: The mean value of regional renal blood flow (rRBF) on the right side was significantly higher than that on the left. The agreements between QISS-MRA and CE-MRA concerning the assessment of absence or presence of an aberrant artery and renal arterial stenosis were perfect. The mean renal volumes measured in the right kidney with QISS-MRA were lower than the corresponding values of CE-MRA. In contrast, the mean renal volumes measured in the left kidney with both MRA techniques were similar. The correlation between the GFRG and rRBF was compared in the same manner as that between GFRCKD-EPI and rRBF. - CONCLUSION: The combination of pCASL and QISS-MRA constitute a reliable preoperative protocol with a total measurement time of <10 min without the potential side effects of gadolinium-based contrast agents or radiation exposure.